2018
DOI: 10.3892/ol.2018.7983
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑125a‑5p inhibits invasion and metastasis of gastric cancer cells by targeting BRMS1 expression

Abstract: Abstract. Accumulating studies have demonstrated microRNAs (miRNAs/miRs) have an important role in multiple processes of human malignant tumor development and progression. Decreased expression of miR-125a-5p has been observed in several types of cancer, including gastric cancer (GC). However, the mechanism and exact function of miR-125a-5p in GC have not been largely elucidated. In the present study, reverse transcription-quantitative polymerase chain reaction indicated that the expression of miR-125a-5p was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…9D). To confirm the above conclusion, miR-125a-5p inhibitors were synthesized and transfected into GES-1 cells, which exhibit high levels of miR-125a-5p expression 22 and low levels of FOXS1 expression. The RT-PCR results showed that the expression of miR-125a-5p was inhibited after transfection with miR-125a-5p inhibitors, with no change in the mRNA levels of FOXS1 (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…9D). To confirm the above conclusion, miR-125a-5p inhibitors were synthesized and transfected into GES-1 cells, which exhibit high levels of miR-125a-5p expression 22 and low levels of FOXS1 expression. The RT-PCR results showed that the expression of miR-125a-5p was inhibited after transfection with miR-125a-5p inhibitors, with no change in the mRNA levels of FOXS1 (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…In this study, we observed the expression of miR-125a-5p and miR-141-3p, largely because previous studies have reported that these have a relatively clear correlation with cancer. It is reported that the decrease of miR-125a-5p expression in gastric cancer is closely related to tumorigenesis and poor prognosis [16], and miR-125a-5p can inhibit the invasion and migration of hepatic cancer cells by regulating the activity of the PI3K/AKT/mTOR pathway [17].On the other hands, high levels of miR-141-3p expression have been reported to target PTEN, which in turn leads to activation of the PI3K-Akt pathway [18]. In this study, the expression levels of exosomal miR-141-5p and miR-125a-5p, as well as the miR-141-5p/miR-125a-5p ratio, were determined.…”
Section: Discussionmentioning
confidence: 99%
“…Since TRIM7 also promoted the ubiquitination of BRMS1, these studies suggest that TRIM7 and BRMS1 may closely interact with each other in osteosarcoma cells. BRMS1 was first found in breast cancer, and its anti-metastasis functions were also confirmed in other cancers such as osteosarcoma, prostate, gastric and lung cancer [15] , [16] , [17] , [18] , where lower expression of BRMS1 was associated with increased cancer cell metastasis. Additionally, knockdown of BRMS1 displays mesenchymal characteristics and enhances cell invasion and migration, along with decreased E-cadherin and increased Vimentin and Twist1 [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%